PENGEMBANGAN LKPD MATEMATIKA BERBASIS ETNOMATEMATIKA RUMAH ADAT BUMI SERENTAK BAK REGAM PADA MATERI GARIS DAN SUDUT DI KELAS V SD - Viola Ananta; Eka Sastrawati; Andi Gusmaulia Eka Putri (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Mathematics learning in elementary schools still faces challenges in students’ understanding of abstract concepts, particularly in lines and angles, which are not yet supported by contextual teaching materials based on local culture. Moreover, the development of ethnomathematics-based worksheets remains limited, resulting in a gap between mathematical concepts and students’ real-life experiences. This study aimed to develop and evaluate the feasibility of an ethnomathematics-based mathematics worksheet using the context of the Bumi Serentak Bak Regam traditional house for fifth-grade students. This study employed a Research and Development method using the ADDIE model, consisting of the stages of analysis, design, development, implementation, and evaluation. Data were collected through validation questionnaires from material, pedagogical, and language experts, as well as response questionnaires from teachers and students. The results showed that the developed worksheet achieved a very high level of validity, with average scores of 4.7 from material experts, 4.7 from pedagogical experts, and 4.9 from language experts. The practicality test results indicated an average score of 5 from teachers and 4.69 from students, both categorized as very practical. These findings indicate that integrating ethnomathematics into learning materials is not only feasible but also has the potential to enhance conceptual understanding through culturally contextual learning. The implication of this study suggests that local culture-based teaching materials can serve as an effective strategy to improve mathematics learning quality while strengthening students’ cultural identity. ABSTRAK Pembelajaran matematika di sekolah dasar masih menghadapi permasalahan rendahnya pemahaman konsep abstrak, khususnya pada materi garis dan sudut, yang belum didukung oleh bahan ajar kontekstual berbasis budaya lokal. Selain itu, pengembangan LKPD yang mengintegrasikan etnomatematika masih terbatas, sehingga belum optimal dalam menjembatani konsep matematika dengan pengalaman nyata peserta didik. Penelitian ini bertujuan untuk mengembangkan dan menguji kelayakan LKPD matematika berbasis etnomatematika dengan konteks Rumah Adat Bumi Serentak Bak Regam pada materi garis dan sudut kelas V SD. Penelitian ini menggunakan metode Research and Development dengan model ADDIE yang meliputi tahap analyze, design, development, implementation, dan evaluation. Instrumen penelitian berupa angket validasi ahli materi, pedagogis, dan bahasa, serta angket respon guru dan siswa. Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan memiliki tingkat validitas sangat tinggi dengan skor rata-rata ahli materi 4,7, ahli pedagogis 4,7, dan ahli bahasa 4,9. Uji kepraktisan menunjukkan skor rata-rata 5 dari guru dan 4,69 dari siswa, yang termasuk kategori sangat praktis. Temuan ini mengindikasikan bahwa integrasi etnomatematika dalam LKPD tidak hanya layak digunakan, tetapi juga berpotensi meningkatkan pemahaman konsep melalui pendekatan kontekstual berbasis budaya. Implikasi penelitian ini menunjukkan bahwa pengembangan bahan ajar berbasis kearifan lokal dapat menjadi strategi efektif dalam meningkatkan kualitas pembelajaran matematika sekaligus memperkuat identitas budaya peserta didik.